The factors of acceptance of children with autism spectrum disorders in preschool institutions - Kojić, Miroslava B.; Kojić Grandić, Smiljana S.; Markov, Zagorka T. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2020)
The present study examines the extent to which the readiness of children and their parents influences the acceptance of children with autism spectrum disorders by their typically developed peers, in regular educational groups. A total of (N=65) of typically developed respondents, attending three preparatory groups for starting school, participated in this research. In each group, one child with an autistic spectrum disorder was included in the educational process. The goal of the study was to determine whether the readiness of typically developed children and their parents influences the peer-acceptance of children with autism spectrum disorders in regular educational groups. The first educational group (N=25) and their parents were prepared for the arrival of a child with an autism spectrum disorder by the preschool teacher. This process also included the parents of the child with an autism spectrum disorder. The cooperation between the preschool teacher and the parents was exquisite. The second educational group (N=25) and their parents were also prepared for the arrival of the child with an autism spectrum disorder, but the cooperation with the parents of the child with an autism spectrum disorder was poor. The third educational group (N=15) was not prepared for the arrival of the child with an autism spectrum disorder to the educational group. The cooperation with the parents was completely lacking. The findings of the study indicate that the child from the first educational group was accepted by its peers the most at the start and the end of the school year, compared to the children from the second and third educational groups. It can be concluded that the readiness of typically developed children and their parents has positive effects on the peer-acceptance of the child with an autism spectrum disorder. The findings indicate the need for further research that will address this topic and its possible implications in practice.